Disiplin Kerja Pegawai Pada Satuan Polisi Pamong Praja Kota Padang - Fira Lailatul Badri; Nelfia Adi; Ahmad Sabandi; Enceria Damanik (Jurnal Imiah Pengabdian Pada Masyarakat (JIPM), 2026)
This study aims to describe the level of work discipline among employees of the Satuan Polisi Pamong Praja Kota Padang. This study was motivated by the occurrence of work discipline violations within Satuan Polisi Pamong Praja Kota Padang, such as tardiness, non-compliance with uniform regulations, unexcused absences, and employees failing to carry out work orders, with a trend of increase from 7 cases (2023) to 16 cases (2024) and 10 cases (2025). This study is a quantitative descriptive study with a population of 469 employees and a sample of 83 individuals determined using the Slovin formula with the Proportionate Stratified Random Sampling technique. Data were collected through a Likert-scale questionnaire that had been tested for validity and reliability, and then analyzed using the mean formula. The results of the study indicate that the work discipline of employees at the Satuan Polisi Pamong Praja Kota Padang falls into the high category, specifically in the aspects of punctuality with an average of 4.32, compliance with rules at 4.48, attendance at 4.40, and responsibility in performing duties at 4.42, with an overall average score of 4.41. Overall, employee work discipline is already classified as high; however, guidance and supervision still need to be improved, particularly regarding the effective use of working hours, so that employee work discipline can be more optimal and consistent.